HUBUNGAN KARAKTERISTIK BOARD DAN KUALITAS SUSTAINABILITY REPORTING YANG DIMODERASI OLEH EXTERNAL ASSURANCE - Tiara Pradani; Rahayu Lestari (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the relationship between the characteristics of the board and the quality of the sustainability report moderated by external assurance. The method used in this study is quantitative by analyzing data from annual reports and sustainability reports of all companies listed on the Indonesia Stock Exchange from 2014 to 2017. The results showed that board of directors size and women on board of directors had no relationship with the quality of the sustainability report. This study also indicates that the board of directors meeting negatively affects the quality of the sustainability report. Furthermore, related to external assurance, which is the moderation in this study, the study results show that external assurance services weaken the relationship between the board of directors size and the quality of sustainability reporting. The use of external assurance services and the relationship between the board of directors meetings and women on board of directors on the quality of sustainability reporting found no influence. This research is limited to companies that issue a separate Sustainability Report (stand-alone sustainability report).